Katherine Mansfield’s Alternative Selves in ‘Bliss’ and ‘The Garden Party’ - Alan Ali Saeed (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
This paper explores the notion of ‘crossing’ in the space between Wellington, the capital of New Zealand, and London in terms of Élan Vital and Bergson a concept that will be applied to Katherine Mansfield’s alternative selves and intuitive memories. It will assess certain related key elements concerning the nature of Mansfield’s professional self-image as a writer expressed in a specifically modernist fashion in her fiction. Such aspects include: the effects upon her understanding of the aesthetics and formal properties of her own writing; the role of her conscious experiences as a woman in society; and how both of these were reflected and interpreted in her stories, ‘Bliss’ (1920) and ‘The Garden Party’ (1922), with reference to Henri Bergson’s Creative Evolution (1907). Also the paper draws a comparison between Mansfield and her Edwardian aunt, Elizabeth Von Arnim, considering how they both cross from the new world into the old, a transition explored particularly through their subjective experiences. Mansfield’s feminist consciousness was indirectly represented through her short stories and fictional characters, while Von Arnim deals with it directly through her autobiographical writing about herself, predominantly in Elizabeth and her German Garden (1898). In this text, Von Arnim turns to her inner life directly by describing how she created a garden, a process judged in its opposition to her dissatisfaction with the Prussian aristocrat she had marred after crossing from New Zealand to Europe. A key figure – albeit now largely a forgotten one – in turn-of-the-century feminism and women’s writing, she was an extremely popular writer whose influence on the following generation such as Mansfield was strong. Arguably, she lived out her élan vital more directly than the succeeding generation – with the exception of such figures as Gertrude Stein. My argument will focus upon and explore Mansfield’s use of modernist stream of consciousness within omniscient narration in contrast with Von Arnim’s autobiographical narrative technique, how it relates to characters in the texts and also in respect to elements of the gendered value of the subjective versus the social, public selves determined by patriarchy.